2015
DOI: 10.1111/cen.12965
|View full text |Cite
|
Sign up to set email alerts
|

The association of thiol/disulphide homeostasis and lipid accumulation index with cardiovascular risk factors in overweight adolescents with polycystic ovary syndrome

Abstract: Objective To assess thiol/disulphide homeostasis and lipid accumulation product index, and to determine whether they are associated with increased cardiovascular disease (CVD) risk or not in overweight adolescents with polycystic ovary syndrome (PCOS). Design Case-control study. Setting Education and Research Hospital. Patients Group 1: 43 overweight+PCOS, Group 2: 45 normal weight+PCOS, Group 3: 27 overweight adolescents and Group 4: 96 age-matched, normal weight healthy controls. Interventions Serum lipid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
(105 reference statements)
1
18
0
1
Order By: Relevance
“…Increased triglycerides, total‐ and LDL‐cholesterol and decreased HDL‐cholesterol concentrations represent a common and consistent lipid disturbance in subjects with PCOS starting to appear in the second decade of life . Elevated lipid profiles in persons with PCOS would result in increased risk of CVD . CoQ10 intake decreasing oxidative stresses and participation in endothelial metabolism may result in an improvement of lipid profiles …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased triglycerides, total‐ and LDL‐cholesterol and decreased HDL‐cholesterol concentrations represent a common and consistent lipid disturbance in subjects with PCOS starting to appear in the second decade of life . Elevated lipid profiles in persons with PCOS would result in increased risk of CVD . CoQ10 intake decreasing oxidative stresses and participation in endothelial metabolism may result in an improvement of lipid profiles …”
Section: Discussionmentioning
confidence: 99%
“…31,32 Elevated lipid profiles in persons with PCOS would result in increased risk of CVD. 33 CoQ10 intake decreasing oxidative stresses and participation in endothelial metabolism may result in an improvement of lipid profiles. 13 This research had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…these findings demonstrated that tDH was impaired in obese adults, which ultimately led to OS. As in this study, tDHimpairment was reported in obese adolescents with polycystic ovary syndrome by Ozler et al (2016) and in obese children by elmas et al (2017). Any change in the thiol/disulphide balance in favor of an increasing disulphide formation causes physiological and structural pathologies in various Simsek et al 2016).…”
Section: Discussionsupporting
confidence: 77%
“…Elevated lipid profiles in subjects with PCOS would result ▶table 1 General characteristics of study participants. in increased risk of CVD [37]. Several mechanisms can explain the beneficial effects of combined calcium-vitamin D supplementation on serum triglycerides and VLDL-cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%